A novel absorptive/reflective solar concentrator for heat and electricity generation: An optical and thermal analysis. (15th April 2016) - Meng, Xian-long; Sellami, Nazmi; Knox, Andrew R.; Montecucco, Andrea; Siviter, Jonathan; Mullen, Paul; Ashraf, Ali; Samarelli, Antonio; Llin, Lourdes F.; Paul, Douglas J.; Li, Wen-guang; Paul, Manosh C.; et al.
Highlights: A novel absorptive/reflective solar concentrator is proposed. The overall optical efficiency reaches up to 94% using truncated area as absorptive element. An optimum concentration ratio of 3.6×/4.0× is found to produce higher total efficiency. A simple model of bare surface with no water flow is studied and discussed. The experimental verification is adopted and it agrees well with the simulations. Abstract: The crossed compound parabolic concentrator (CCPC) is one of the most efficient non-imaging solar concentrators used as a stationary solar concentrator or as a second stage solar concentrator. In this study, the CCPC is modified to demonstrate for the first time a new generation of solar concentrators working simultaneously as an electricity generator and thermal collector. The CCPC is designed to have two complementary surfaces, one reflective and one absorptive, and is named as an absorptive/reflective CCPC (AR-CCPC). Usually, the height of the CCPC is truncated with a minor sacrifice of the geometric concentration. These truncated surfaces rather than being eliminated are instead replaced with absorbent surfaces to collect heat from solar radiation. The optical efficiency including absorptive/reflective part of the AR-CCPC was simulated and compared for different geometric concentration ratios varying from 3.6× to 4×. It was found that the combined optical efficiency of the AR-CCPC 3.6×/4× remained constant and high all day long and that it had the highest total optical efficiency compared to other concentrators. In addition, the temperature distributions of AR-CCPC surfaces and the assembled solar cell were simulated based on those heat flux boundary conditions. It was shown that the addition of a thermal absorbent surface can increase the wall temperature. The maximum value reached 321.5 K at the front wall under 50° incidence. The experimental verification was also adopted to show the benefits of using absorbent surfaces. The initial results are very promising and significant for the enhancement of solar concentrator systems with lower concentrations.